E-Governance in Practice: A Study of Online Public Grievance Redressal in Karnataka - Prakasha G.V., (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2026)
In this paper, we take a closer look at the impressive progress made by the Government of Karnataka in resolving public grievances digitally over the period of time in various departments under the state government. It focuses on the significant impact made on lives of common man by improving the effectiveness, efficiency, transparency, and accountability of governance processes, services, and decision-making. The integrated Public Grievance Redressal System (iPGRS) is an online platform available to the citizens to lodge their grievances to the public authorities on any subject related to service delivery in Karnataka. It was launched on 1st November 2021. It is a single portal connected to more than 40 Department schemes/ services delivered by the Government of Karnataka. It discusses how efficient iPGRS in the redressal of public grievances. This research article evaluates the performance and effectiveness of IPGRS–Janaspandana in Karnataka during the period 2024–2025.
Keywords: E-Governance; Public Grievance Redressal; iPGRS; Janaspandana; Digital Governance; Karnataka